The feasibility and generalizability of assessing the appropriateness of antimicrobial prescribing in hospitals: a review of the Australian National Antimicrobial Prescribing Survey. Issue 1 (9th February 2022) - James, Rodney; Nakamachi, Yoshiko; Morris, Andrew; So, Miranda; Ponnampalavanar, Sasheela Sri La Sri; Chuki, Pem; Loong, Ly Sia; Lai, Pauline Siew Mei; Chen, Caroline; Ingram, Robyn; Rajkhowa, Arjun; Buising, Kirsty; et al.
Abstract: The National Antimicrobial Prescribing Survey (NAPS) is a web-based qualitative auditing platform that provides a standardized and validated tool to assist hospitals in assessing the appropriateness of antimicrobial prescribing practices. Since its release in 2013, the NAPS has been adopted by all hospital types within Australia, including public and private facilities, and supports them in meeting the national standards for accreditation. Hospitals can generate real-time reports to assist with local antimicrobial stewardship (AMS) activities and interventions. De-identified aggregate data from the NAPS are also submitted to the Antimicrobial Use and Resistance in Australia surveillance system, for national reporting purposes, and to strengthen national AMS strategies. With the successful implementation of the programme within Australia, the NAPS has now been adopted by countries with both well-resourced and resource-limited healthcare systems. We provide here a narrative review describing the experience of users utilizing the NAPS programme in Canada, Malaysia and Bhutan. We highlight the key barriers and facilitators to implementation and demonstrate that the NAPS methodology is feasible, generalizable and translatable to various settings and able to assist in initiatives to optimize the use of antimicrobials.